Omega‐3 fatty acids may prevent long‐term progression to psychosis. Issue 12 (December 2015) - Unknown
Abstract : Extending the findings of previously published research by analyzing results over a longer follow‐up period, a study has found that 12 weeks of treatment with long‐chain omega‐3 polyunsaturated fatty acids reduced the risk of progression to psychotic disorder over a 7‐year period in young people with subthreshold psychotic states.